2003
DOI: 10.1038/sj.cdd.4401247
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of papain-like cysteine proteases and legumain by caspase-specific inhibitors: when reaction mechanism is more important than specificity

Abstract: We report here that a number of commonly used small peptide caspase inhibitors consisting of a caspase recognition sequence linked to chloromethylketone, fluoromethylketone or aldehyde reactive group efficiently inhibit other cysteine proteases than caspases. The in vitro studies included cathepsins B, H, L, S, K, F, V, X and C, papain and legumain. Z-DEVD-cmk was shown to be the preferred irreversible inhibitor of most of the cathepsins in vitro, followed by Z-DEVD-fmk, Ac-YVAD-cmk, Z-YVAD-fmk and Z-VAD-fmk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
165
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 47 publications
6
165
0
Order By: Relevance
“…Although the pancaspase inhibitor zVAD.fmk significantly delays cell death, this finding does not necessarily argue for caspase involvement in B10-induced cell death, because zVAD.fmk can also block other enzymes at the concentration used in this study, such as cathepsins, which have previously been reported to be involved in caspase-dependent and -independent cell death. 13,24 Importantly, this might explain that apoptotic and non-apoptotic modes of cell death can coexist as a consequence of the intracytoplasmic release of lysosomal enzymes upon B10 treatment. Indeed, although cathepsin activity can lead to the activation of substrates specifically involved in apoptosis, such as Bid and caspase-3, 12,14 their ability to cleave a large number of substrates can also commit cells to die via the non-apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pancaspase inhibitor zVAD.fmk significantly delays cell death, this finding does not necessarily argue for caspase involvement in B10-induced cell death, because zVAD.fmk can also block other enzymes at the concentration used in this study, such as cathepsins, which have previously been reported to be involved in caspase-dependent and -independent cell death. 13,24 Importantly, this might explain that apoptotic and non-apoptotic modes of cell death can coexist as a consequence of the intracytoplasmic release of lysosomal enzymes upon B10 treatment. Indeed, although cathepsin activity can lead to the activation of substrates specifically involved in apoptosis, such as Bid and caspase-3, 12,14 their ability to cleave a large number of substrates can also commit cells to die via the non-apoptotic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Clan CA, which includes the lysosomal cathepsins and the calcium-dependent calpains, prefer a hydrophobic or large residue at P2 but have no preference for the P1 residue (Mottram et al 2003). Hence, the alanine in z-VAD and the valine in z-DEVD, comply with clan CA requirements and these inhibitors have indeed been shown to inhibit cathepsin B, another clan CA protease (Rozman-Pungercar et al 2003).…”
Section: A S P a S E-l I K E A C T I V I T Ymentioning
confidence: 99%
“…This can be explained by the fact that, when used at these higher doses, zVAD.fmk is no longer specific and could also inhibit other cysteine proteases, like calpains 13 or cathepsins. 14,15 Within the panoply of other cysteine protease inhibitors tested, the most powerful agents precluding AIF release were: MG101 and calpeptin (calpain inhibitors); zFA.fmk (cathepsin inhibitor); and MG132 (an inhibitor of the proteasome). In a lesser degree, zFY.fmk, CA-074, Ac-LLM-CHO, MG115, and NLVS also inhibit AIF release (Table 1 and Figure 1f-h).…”
mentioning
confidence: 99%